Analisis Perbandingan Pajak Penghasilan Badan Terutang Berdasarkan PP. No. 46/2003 dan UU. No. 36/2008 Pada PT. Toyomas Putra - Rina Suryani; Nurwati Nurwati (ITB Ahmad Dahlan Jakarta, 2019)
The main source of funding for National development is tax, One of tax type that can increase tax revenues is income tax. The purpose of this study is to determine the application of PP No. 46 Year 2013 compared with UU No. 36 Year 2008 to calculate amount of income tax PT Toyomas Putra in fiscal year. This study uses comparative descriptive analysis techniques. The results showed for 2017 the amount of income tax calculate with PP No. 46 Year 2013 is cheaper if compared with UU No. 36 Year 2008. The results of income tax calculate with PP No. 46 Year 2013 is Rp.42.042.777,00. The results of income tax calculate with UU No. 36 Year 2008 is Rp.84.920.573,00.